2014
DOI: 10.1093/jisesa/ieu141
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antibiotics Gentamicin on the Postembryonic Development of Chrysomya putoria (Diptera: Calliphoridae)

Abstract: We evaluate the effects the antibiotic Gentamicin on the development of Chrysomya putoria (Wiedemann, 1818). Third-generation, first-instar larvae were reared in a climatic chamber on 60 g of homogenate + agar 65% and were treated with three concentrations of Gentamicin: 4.44 mg/ml, 13.33 mg/ml, and 66.66 mg/ml. The control consisted of distilled water. The relationships between mean body mass of mature larvae (measured after diet abandonment, in batches of five individuals), duration of larval and pupal stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The growth, weight and survival were not altered by therapeutic antibiotic doses. The development of Chrysomya putoria (Wiedemann, 1830) maggots was not altered by the antibiotic gentamicin (Ferraz et al, 2014). The examination of the effects of ceftriaxone and levofloxacin on the development of Calliphora vomitoria (Linnaeus, 1758) revealed that levofloxacin delayed the maggot development and that the pupation was delayed when both antibiotics were applied (Preußer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The growth, weight and survival were not altered by therapeutic antibiotic doses. The development of Chrysomya putoria (Wiedemann, 1830) maggots was not altered by the antibiotic gentamicin (Ferraz et al, 2014). The examination of the effects of ceftriaxone and levofloxacin on the development of Calliphora vomitoria (Linnaeus, 1758) revealed that levofloxacin delayed the maggot development and that the pupation was delayed when both antibiotics were applied (Preußer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On this subject, Ferraz et al . (, b; ) tested the development of C . putoria using a diet‐containing antibiotics (ampicillin, gentamicin and ciprofloxacin) in different concentrations, to study the species' growth rate under the effect of these substances.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic wound debridement therapy with larvae is simple, and highly effective. It can even be used in patients undergoing antibiotic therapy without the danger of these interfering with the therapeutic action of the larvae (Ferraz et al 2014). It is indicated for different types of infected wounds and its effectiveness has already been widely proven (Sherman et al 2013, Siribumrungwong et al 2018, Borkataki et al 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The mastery of breeding techniques for this species enables obtaining females with a high capacity for oviposition, generating a large amount of egg masses to be submitted to the sterilization process, which is an important prerequisite for its use in biotherapy. In addition, the possibility of storing the larvae obtained under refrigeration improves their distribution logistics for use (Dallavecchia et al 2015, Ferraz et al 2014.…”
Section: Introductionmentioning
confidence: 99%